Analysis of character education management at modern Islamic boarding schools - Riduansyah, Achmad; Aslamiah, Aslamiah; Saleh, Muhammad (Curricula: Journal of Curriculum Development, 2026)
Modern Islamic boarding schools (Pesantren) function as total institutions providing 24-hour character education. This qualitative study, employing a multi-site design at MA Darul Hijrah and MA Puteri Annajah, aims to analyze character education management through three focal points: planning, implementation, and monitoring/evaluation. Findings reveal that planning is conducted systematically and participatively through leadership councils, guided by the Panca Jiwa values (sincerity, simplicity, self-reliance, Islamic brotherhood, and freedom). Implementation is carried out through an integrative "tripod tarbiyah" model that synchronizes intra- and extra-curricular activities with those in the dormitories, with teachers and wardens serving as primary role models. Furthermore, monitoring and evaluation are carried out continuously through multi-layered supervision systems and collective evaluation meetings. Despite challenges from digital culture, both institutions demonstrate high effectiveness in shaping student character. It is driven by visionary leadership, cross-departmental collaboration, and a consistent culture of deliberation. The study concludes that the key to successful character education in modern pesantren is aligning the leader’s vision with structured, integrated managerial governance.